Pengaruh Stres Kerja, Disiplin Kerja, dan Kepercayaan Karyawan terhadap Komitmen Organisasi : (Studi Penelitian pada Karyawan PT Brataco Cabang Jakarta Barat) - Yoel Wijaya; Aris Wahyu Kuncoro (Universitas 45 Surabaya, 2024)
This study aims to examine the influence of Work Stress, Work Discipline, and Employee Trust on Organizational Commitment in employees of PT. Brataco West Jakarta Branch. This study uses a Non Probability Sampling technique with a saturated sampling type taken as many as 53 employees of PT. Brataco West Jakarta Branch as a respondent in this study. Data was collected through a questionnaire with a Likert scale processed using Microsoft Excel 2010 software, as well as SPSS version 26 software. The research method used is multiple linear regression. The results of this study show that the variables of Work Stress (0.035) and Employee Trust (0.212) both have a positive and significant effect on Organizational Commitment. Meanwhile, the Work Discipline variable has no effect and is not significant to Organizational Commitment. The results of this study are expected to increase the level of organizational commitment in PT. Brataco West Jakarta Branch.